The Influence Of Consumer Behavior On Purchasing Decisions Of Beauty Products On E-Commerce Platforms In South Jakarta - Lia Siti Julaeha; Natasha Adistya Puteri (CV. Aksara Global Akademia, 2024)
This writing aims to examine the influence of Consumer Behavior on the Purchase Decision of Beauty Products on e-commerce platforms in South Jakarta. The population in this study consists of individuals who purchase beauty products using e-commerce in South Jakarta. and the exact number is unknown. The sampling technique employed is Accidental Sampling using the Lemeshow formula. with a sample size of 68 respondents. The data collection method utilized is a questionnaire. The data analysis techniques include descriptive analysis. quantitative analysis. simple regression analysis. hypothesis testing (t-test). and coefficient of determination. processed using Statistical Product and Service Solution (SPSS) version 25.0. The research findings indicate that Consumer Behavior has a positive and significant influence on the Purchase Decision of Beauty Products on e-commerce platforms in South Jakarta.